2011
DOI: 10.1007/s13187-011-0286-z
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Genetic Testing to Identify Hereditary Colorectal Cancer: Perspectives of High-Risk Patients, Community Members, and Clinicians

Abstract: The aim of this study was to establish key characteristics that patients, consumers, and health professionals value regarding genetic testing (GT) and personalized medicine using the example of GT for hereditary Lynch syndrome. We conducted a series of focus groups with individuals recruited from a clinic that follows those at high risk for hereditary cancer, individuals recruited from the community, physicians, and genetic counselors. Participants were presented with clinical scenarios about Lynch syndrome te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Other studies of screening and genetic testing suggest that the ability of test results to inform decision making about prevention or therapeutic interventions is important (Andrykowski et al 1996;Mesters et al 2005;Ramsey et al 2003;Rose et al 2005;Wakefield et al 2007;Walsh et al 2012), and genetic exceptionalism may be reduced when active preventive strategies are available (Ross 2001;Saukko et al 2006). Our findings are consistent with this, although require further examination given the stated limitations.…”
Section: Discussionsupporting
confidence: 83%
“…Other studies of screening and genetic testing suggest that the ability of test results to inform decision making about prevention or therapeutic interventions is important (Andrykowski et al 1996;Mesters et al 2005;Ramsey et al 2003;Rose et al 2005;Wakefield et al 2007;Walsh et al 2012), and genetic exceptionalism may be reduced when active preventive strategies are available (Ross 2001;Saukko et al 2006). Our findings are consistent with this, although require further examination given the stated limitations.…”
Section: Discussionsupporting
confidence: 83%
“…6,7 This strategy can identify a significant number of Lynch syndrome patients. [8][9][10] A description of genomic sequence and a listing of mutations and single-nucleotide polymorphisms (SNPs) for genes is provided in this document. The entire genomic sequence along with the structural motifs of the genes described in this document can be found at http://www.genome.ucsc.edu.…”
mentioning
confidence: 99%
“…To construct the DCE used for this study, possible attributes were identified from previously published studies, [21][22][23][24]27 six expert interviews (ie, a scientist with a specific interest in public health genomics, a scientist with a specific interest in ethics of genetics/genomics, a specialist in cancer genetics and three medical specialists in gastroenterology) and five group interviews (n = 38) with the target population of men and women aged 55-65 years. These group interviews were conducted using the Nominal Group Technique.…”
Section: Dce Developmentmentioning
confidence: 99%
“…22,37 Optimal communication may improve knowledge among the general population and may facilitate informed decision making among individuals who are offered genetic screening. First, respondents deemed survival probability as a highly important test characteristic of genetic screening.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation